Pemanfaatan Limbah Cair Tahu menjadi Biogas di Industri Tahu Murni Pak Min Jomblangan, Banguntapan, Yogyakarta - Lukhi Mulia Shitophyta; Siwi Purwanti; Maryudi Maryudi (Universitas Mathla'ul Anwar Banten, 2019)
COMMUNITY PARTNERSHIP PROGRAM: THE UTILIZING OF TOFU LIQUID WASTE INTO BIOGAS AT TOFU INDUSTRY OF PAK MIN, JOMBLANGAN, BANGUNTAPAN, YOGYAKARTA. The industry tofu of Pak Min is a home industry with four employees which produces 200 kg of tofu every day and generates 50 kg of liquid wastes per day. The problem that is faced by the industrial owner is the lack of knowledge in handling liquid wastes. The disposal of waste is only discharged into a river which results in buildup of liquid paddles on the ground surface and environmental pollution. Therefore, the objectives of this program were to socialize the hazard and management process of tofu waste and to provide the training to convert tofu liquid waste into biogas.